2019
DOI: 10.1007/s12033-019-00199-x
|View full text |Cite
|
Sign up to set email alerts
|

The Biogenetic Origin of the Biologically Active Naematolin of Hypholoma Species Involves an Unusual Sesquiterpene Synthase

Abstract: Naematolin is a biologically active sesquiterpene produced by Hypholoma species. Low titres and complex structure constrain the exploitation of this secondary metabolite. Here, we de novo sequenced the H. fasciculare genome to identify a candidate biosynthetic gene cluster for production of naematolin. Using Aspergillus oryzae as a heterologous host for gene expression, the activity of several sesquiterpene synthases were investigated, highlighting one atypical sesquiterpene synthase apparently capable of cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Seven verified constructs-pTYGS-argHfasTerp179, pTYG-argCop-1, pTYG-argCop-2, pTYG-argCop-3, pTYG-argCop-4, pTYG-argOmp6, and pTYG-argOmp7-were independently transferred to A. oryzae strain NSAR1 protoplasts via polyethylene glycol (PEG)-mediated transformation reactions. Subsequent gas chromatography-mass spectrometry (GC-MS) analysis on previous (pTYGS-argHfasTerp94a, pTYGS-argHfasTerp94b, and pTYGS-argHfasTerp344) and current transformants confirmed our previous results of HfasTerp94a, HfasTerp94b, and HfasTerp344 (Al-Salihi et al, 2019) through the replication of humulene and caryophyllene production, although at lower levels. The production of most of the major products of the two controls, pTYG-argCop-3 and pTYG-argCop-4, were confirmed as well as the previously uncharacterized humulene in the Cop-3 extract (Figure 8 and Supplementary Figure 33).…”
Section: Heterologous Expression Of Selected Sesquiterpene Synthasessupporting
confidence: 83%
See 4 more Smart Citations
“…Seven verified constructs-pTYGS-argHfasTerp179, pTYG-argCop-1, pTYG-argCop-2, pTYG-argCop-3, pTYG-argCop-4, pTYG-argOmp6, and pTYG-argOmp7-were independently transferred to A. oryzae strain NSAR1 protoplasts via polyethylene glycol (PEG)-mediated transformation reactions. Subsequent gas chromatography-mass spectrometry (GC-MS) analysis on previous (pTYGS-argHfasTerp94a, pTYGS-argHfasTerp94b, and pTYGS-argHfasTerp344) and current transformants confirmed our previous results of HfasTerp94a, HfasTerp94b, and HfasTerp344 (Al-Salihi et al, 2019) through the replication of humulene and caryophyllene production, although at lower levels. The production of most of the major products of the two controls, pTYG-argCop-3 and pTYG-argCop-4, were confirmed as well as the previously uncharacterized humulene in the Cop-3 extract (Figure 8 and Supplementary Figure 33).…”
Section: Heterologous Expression Of Selected Sesquiterpene Synthasessupporting
confidence: 83%
“…Our previous genomic investigation of Hypholoma suggested that only terpenoid compounds were produced, with a range of cyclization patterns ( Al-Salihi et al, 2019 ). However, a subsequent in-depth BLAST search of functionally characterized core enzymes selected from different fungi resulted in the identification of additional biosynthetic gene clusters (BGCs) in both Hypholoma species (see Supplementary Tables 1 , 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations